Highly Fluorinated Trianglimine Macrocycles: A Supramolecular Organic Framework - Kunde, Tom; Pausch, Tobias; Reiss, Guido J.; Schmidt, Bernd M. (Synlett, 2021)
A novel highly fluorinated dialdehyde was prepared by a two-stage synthesis. This reactive building block for dynamic imine chemistry was used in a condensation reaction to generate the first extensively fluorinated trianglimine. An analysis of the material properties and, especially, the crystal structure of the [3+3] macrocycle revealed a supramolecular organic framework with tubular porous channels. The use of fluorinated ligands to generate hydrophobic electron-deficient channel-like pores is an important addition to the ever-expanding field of supramolecular networks and to trianglimine chemistry in general.
Keywords: supramolecular organic frameworks; trianglimines; porous materials; fluorinated ligands; crystal structure